Original paperOptimism as a predictor of health-related quality of life in psoriatics - Miniszewska, Joanna; Chodkiewicz, Jan; Ograczyk, Alicja; Zalewska-Janowska, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction : Psoriasis is a chronic and relapsing disease which significantly affects the quality of life and social functioning of the affected people. It is one of the so-called psychodermatological diseases, which means that there exists a psychological component in the image of the disease. Aim : To examine the relationship between health-related quality of life (HRQoL) in psoriatics and selected demographic, medical and psychological (dispositional optimism) variables and to determine the predictors of HRQoL in the examined group. Material and methods : The study consisted of 138 patients with the diagnosis of psoriasis vulgaris. Most respondents (125) had psoriasis on exposed parts of the body. Methods used: SKINDEX, Life Orientation Test, PASI. Results : The gender does not differentiate patients in terms of HRQoL and optimism. Almost all of analyzed variables correlate with HRQoL and all examined variables explain the results variability for overall HRQoL but only optimism explains the highest percentage of the variability (β = –0.35). Conclusions : The study demonstrated a very interesting relationship – the stronger optimism the better quality of life in psoriatics. So, a generalized expectation of positive life events is related to better assessment of HRQoL.